Combined Methods of Detoxification of Antinutrients that Prevent Jatropha Caucas to Take its Place in Aninmal Feed (Global Journal of Science Frontier Research, 2019)
A study was conducted to evaluate the chemical composition and antinutrient qualities of Jatropha seeds detoxified by physical, chemical, biological, and combined method, making four (4) treatment all together.100kg of jatropha seeds was detoxified each by physical (grind, soak and sundry) chemical (soak in methylated sprit, hexan and methanol) biological (Aspergillus niger and Bacillus lichiformis) and combined method ( all the previous methods is repeated in this method).Quantitative analysis of antinutrients from each of the methods was carried out and the result revealed, a drastical reduction of about (70%) of phobol ester and other antinutrients in combined method of detoxification was noticed.
Keywords: jatropha curcas; aspergillus niger; baccillus lichiformis; fermentation; antinutrients